Effect of sowing time and spacing on lettuce seed production in hilly region - Firoz, ZA; Alam, MS; Uddin, MS; Khatun, SA (Bangladesh Journal of Agricultural Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI: 10.3329/bjar.v34i3.3980 Bangladesh J. Agril. Res. 34(3) : 531-536, September 2009